Developing a community-informed sexual and gender minority health research training program in the Deep South - Emma Sophia Kay; Gabe H. Miller; Frank Puga; Josh Bruce; Bridge Hill Kennedy; Gregory M. Pavela; Erin Densley; Trevis Smith; Mallie Froehlich; Sarah MacCarthy (Frontiers in Public Health)
The largest sexual (e.g., lesbian, gay and bisexual) and gender (e.g., transgender, nonbinary, gender diverse) minority (SGM) population in the United States resides in the Deep South; however, this area has no legal protections for SGM individuals, who experience substantial health inequities. Researchers from the Deep South are consistently overlooked in national dialogs on SGM health, with few SGM health training programs located in this area of the country. In response to these health and sociopolitical disparities and the dearth of regional SGM health training programs, we developed GenderS (Education on Gender and Sex), an innovative research education program led by a community-academic partnership that provides experiential and didactic training in SGM health in the Deep South via an online asynchronous curriculum; a one-week in-person residency in Birmingham, Alabama; and monthly virtual networking salons. In this paper, we describe the theoretical underpinnings of GenderS, the process for developing the curriculum and other program components, our evaluation plan, and lessons learned to date. Through dissemination of a national toolkit that includes templates and examples from GenderS, we can help other organizations adapt our program to their local contexts to train the next generation of SGM health researchers. Although we met challenges in developing recruitment materials for the program due to the enactment of an anti-diversity, equity, and inclusion law in Alabama, enthusiasm for our program remained high, illustrated by receipt of applications from 20 applicants across the United States and Africa.